CCR4+CD8+ T cells clonally expand to differentiated effectors in murine psoriasis and in human psoriatic arthritis. Issue 4 (15th February 2023) - Montico, Guendalina; Mingozzi, Francesca; Casciano, Fabio; Protti, Giulia; Gornati, Laura; Marzola, Erika; Banfi, Giuseppe; Guerrini, Remo; Secchiero, Paola; Volinia, Stefano; Granucci, Francesca; Reali, Eva
Abstract: Psoriasis is a chronic inflammatory skin disease with an autoimmune component and associated with joint inflammation in up to 30% of cases. To investigate autoreactive T cells, we developed an imiquimod‐induced psoriasis‐like inflammation model in K5‐mOVA.tg C57BL/6 mice expressing ovalbumin (OVA) on the keratinocyte membrane, adoptively transferred with OT‐I OVA‐specific CD8 + T cells. We evaluated the expansion of OT‐I CD8 + T cells and their localization in skin, blood, and spleen. scRNA‐seq and TCR sequencing data from patients with psoriatic arthritis were also analyzed. In the imiquimod‐treated K5‐mOVA.tg mouse model, OT‐I T cells were markedly expanded in the skin and blood at early time points. OT‐I T cells in the skin showed mainly CXCR3 + effector memory phenotype, whereas in peripheral blood there was an expansion of CCR4 + CXCR3 + OT‐I cells. At a later time point, expanded OVA‐specific T‐cell population was found in the spleen. In patients with psoriatic arthritis, scRNA‐seq and TCR sequencing data showed clonal expansion of CCR4 + TCM cells in the circulation and further expansion in the synovial fluid. Importantly, there was a clonotype overlap between CCR4 + TCM in the peripheral blood and CD8 + T‐cell effectors in the synovial fluid. This mechanism could play a role in the generation and spreading of autoreactive T cells to the synovioentheseal tissues in psoriasis patients at risk of developing psoriatic arthritis. Abstract : Skin‐primed self‐reactive T cells egressing to the blood cloud localize and clonally expand at distant organs. This mechanism could represent a link between skin and joint manifestations in psoriasis patients at risk of developing psoriatic arthritis.